Activated sludge-degrading analgesic drug acetaminophen: Acclimation, microbial community dynamics, degradation characteristics, and bioaugmentation potential. (1st September 2020) - Park, Sangeun; Oh, Seungdae
Abstract: This study identified specific bacterial populations that play a key role in detoxifying acetaminophen (N-acetyl-p-aminophenol, APAP) in activated sludge (AS) microbial communities. An AS bioreactor was established by feeding 100 mg/L of APAP as a sole carbon, nitrogen, and energy source. While the bioreactor increased APAP biotransformation rates significantly (0.7 d −1 to 6.1 d −1 ) over a month of acclimation, it selected for Pseudomonas by significantly reducing community diversity by 40% and richness by 47%. A Pseudomonas population (designated PCO) isolated from the APAP-degrading community was phylogenetically distinct from other Pseudomonas spp. previously reported as APAP-degrading isolates. PCO could remove APAP at levels up to 590 mg/L without inhibition and could also metabolize APAP-derived metabolites, 4-aminophenol, hydroquinone, and 1, 4-benzoquinone at varying levels. PCO was introduced to AS at various volumes (5, 25, and 50% of the total), showing significantly enhanced APAP transformation rates (1.5, 1.9, and 2.3 d −1 ) compared to the control (1.2 d −1 ) without PCO inoculation. Overall, our study provides new insights into the phylogenetic and metabolic features of a key species population predominantly accelerating APAP breakdown in the context of AS microbial communities, which will help in the design of a biological means (bioaugmentation) of treating APAP-bearing waste streams. Graphical abstract: Image 1 Highlights: Microbial community dynamics of activated sludge-metabolizing acetaminophen was examined. Selection of Pseudomonas was responsible for increasing the community APAP transformation rate. Cell growth and degradation characteristics of APAP and its metabolites by Pseudomonas were elucidated. Bioaugmentation potential of Pseudmonas for APAP detoxification was experimentally validated.